Psychology 3300. Sexual behaviour. Lecture 22. Planned Parenthood - Memorial University of Newfoundland. Division of Extension Service; Hannah, Ted (Memorial University of Newfoundland. Division of Extension Service, 1980)
Dr. Ted Hannah interviews May Johnson, Clinic Director of Planned Parenthood Newfoundland and Labrador. Date from lecture 22. Minor distortion throughout.